2014
DOI: 10.1007/s10964-013-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Related Teasing in the School Environment: Associations with Psychosocial Health and Weight Control Practices Among Adolescent Boys and Girls

Abstract: Weight-related teasing has been found to be associated with low self-esteem, depressive symptoms, body dissatisfaction, and weight control behaviors in adolescents. While research has typically examined weight-related teasing directed towards the individual, little is known about weight-related teasing at the school level. This study aimed to determine the association between the school-level prevalence of weight-related teasing and psychosocial factors, body dissatisfaction and weight control behaviors in ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 39 publications
9
69
0
4
Order By: Relevance
“…The gender differences in the associations between social characteristics and emotional well-being are similar to previous findings (9,43), and may be attributable to differences in the ways in which girls and boys are socialized to respond to peers, social norms and related influences generally. Prior research regarding media influences in particular has shown that social comparison with media figures – a possible pathway in the relationship between media exposure and body image – is stronger for girls than boys (9), which may also explain the present findings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The gender differences in the associations between social characteristics and emotional well-being are similar to previous findings (9,43), and may be attributable to differences in the ways in which girls and boys are socialized to respond to peers, social norms and related influences generally. Prior research regarding media influences in particular has shown that social comparison with media figures – a possible pathway in the relationship between media exposure and body image – is stronger for girls than boys (9), which may also explain the present findings.…”
Section: Discussionsupporting
confidence: 85%
“…Viewing characters’ on-screen experiences, such as weight teasing, may therefore be detrimental to the body satisfaction of young people, similar to weight stigma observed in the real world ( e.g. , in school (43)). Furthermore, research has consistently noted poorer body satisfaction among women and girls and those who are overweight or obese (7); the strength of media influence may further depend on characteristics of on-screen role models, as young people are more likely to identify with characters who are similar to themselves in terms of gender or other characteristics (46).…”
Section: Weight Teasing and Body Satisfactionmentioning
confidence: 98%
See 1 more Smart Citation
“…Observing peer victimization or mistreatment of particular groups (e.g., overweight, LGBT youth) can negatively affect adjustment (e.g., Lampard, MacLehose, Eisenberg, Neumark-Sztainer, & Davison, 2014; Rivers, Poteat, Noret, & Ashurst, 2009). Such observations may promote perceptions of the school environment as unsafe, and negative school climate is linked to poor psychosocial adjustment (e.g., Brand, Felner, Shim, Seitsinger, & Dumas, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a large sample of US adolescents, an association between physical abuse from a partner and extreme weight control behaviours was found, with participants reporting dating violence and rape being more likely to report EXTREME DIETING BEHAVIOURS 4 vomiting, and the use of diet pills and laxatives in order to lose weight than those not reporting such experiences (Ackard and Neumark-Sztainer, 2002). Bullying is associated with weight control behaviours in adolescents (Farrow and Fox, 2011, Gonsalves et al, 2013, Lampard et al, 2014. Less is known about the association between electronic bullying and weight control behaviours, the relevance of which has increased in recent years (Kowalski and Limber, 2013).…”
Section: Abstract: Extreme Dieting Behaviours; Psychosocial Correlatementioning
confidence: 99%